Effects of macroeconomic uncertainty and labor demand shocks on the housing market - Gabriel Lee; Binh Nguyen Thanh; Johannes Strobel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2017)
This paper shows that macroeconomic uncertainty affects the housing market in two significant ways. First, uncertainty shocks adversely a¤ect housing prices but not the quantities that are traded. Controlling for a broad set of variables in fixed-effects regressions, we find that uncertainty shocks reduce both housing prices and median sales prices in the amount of 1.4% and 1.8%, respectively, but the effect is not statistically significant for the percentage changes of all homes sold. Second, when both uncertainty and local demand shocks are introduced, the effects of uncertainty on the housing market dominate that of local labor demand shocks on housing prices, median sell prices, the share of houses selling for loss, and transactions. The aforementioned effects are largest for the states that exhibit relatively high housing price volatilities, suggesting real options effects in the housing market during the times of high uncertainty.
Keywords: E4; E5; E2; R2; R3; 330; Bartik labor demand shocks; time-varying uncertainty shocks; real options effects; housing market